Ethics, equity and community development - Banks, Sarah; Westoby, Peter (Rethinking community development., 2019)
Through a wide range of cross-disciplinary and international perspectives, this book examines the place of ethics and ethical practice in community development work within varied political, ecological and economic contexts across the globe. Contributors examine issues surrounding community development as a profession, roles and boundaries, consent and everyday ethics in order to consider the multiple challenges of negotiating the tensions between ethics and politics in an unequal world.